Freedom and The Role of The Press on Law Enforcement Reviewed in The Perspective of Law Number: 40 Of 1999, Concerning The Press - Satino Satino; Yuliana Yuli W; Iswahyuni Adil (Publikasi Indonesia, 2021)
Law Number 40 of 1999 concerning the Press is one of the legal regulations that have a role in efforts to realize a good life together. The struggle of the Indonesian press to achieve freedom was finally achieved after the enactment of Law Number 40 of 1999 concerning the Press. The purpose of this study is to find out how the freedom and role of the press in law enforcement are reviewed from the perspective of Law Number 40 of 1999, concerning the press. This study uses a sociological juridical method, the results of research conducted on real facts in society with the intent and purpose of finding facts, then proceeding with finding problems, ultimately leading to problem identification and leading to problem solving. The results of the research include the press trying to carry out its functions, rights, obligations, and roles, so the press must respect the human rights of everyone. The press has an important role in realizing Human Rights (HAM), as guaranteed in the Decree of the People's Consultative Assembly of the Republic of Indonesia Number: XVII/MPR/1998. Based on the results of the research above, it is necessary to uphold the freedom of the press in conveying public information in an honest and balanced manner and that freedom of the press is not absolute for the press alone, but to guarantee the rights of the public to obtain information. what happened in the context of realizing press freedom as contained in Law/040/1999 concerning the Press.